Fatigue strength evaluation of case‐hardened components combining heat‐treatment simulation and probabilistic approaches - Iss, Valérian; Meis, Jean‐André; Rajaei, Ali; Hallstedt, Bengt; Broeckmann, Christoph (Fatigue & fracture of engineering materials & structures, 2024)
In order to raise the hardness and strength of the surface layer of mechanical components and induce favorable residual compressive stresses, case‐hardening procedures have become established in the heat treatment of steel. In this work, a calculation concept for the fatigue strength of components that have been case‐hardened through carburizing heat treatment is being developed. The residual stress and the load stresses in complex‐shaped, carburized materials are determined using a finite element (FE) model. The fatigue limit of the components is derived using probabilistic methods and taking into account hardness gradients, residual stresses, and non‐metallic inclusions. The model is validated with available axial bending fatigue test data and then used to predict the rotating bending fatigue limit of samples with various geometries and heat‐treatment conditions. This work demonstrates the capability of combining probabilistic and FE‐based modeling to represent complex interactions between variables that affect the fatigue of heat‐treated components, such as steel cleanliness, notch shape, case‐hardening depth, or loading conditions. Highlights Combined FE‐based and probabilistic methods can predict fatigue strength accurately. Interplay of heat‐treatment output, geometry, load, and material is considered. Crack initiation position gets shifted by increased case‐hardness depth. Fatigue strength reduction due to defects in steel depends on load concentration.